Effect of Low-Frequency Alternative-Current Magnetic Susceptibility in Ni80Fe20 Thin Films. (15th May 2012) - Chen, Yuan-Tsung; Lin, S. H.; Lin, Y. C.
Abstract : X-ray diffraction (XRD) results indicate that the NiFe thin films had a face-centered cubic (FCC) structure. Post-annealing treatment increased the crystallinity of NiFe films over those at room temperature (RT), suggesting that NiFe crystallization yields FCC (111) texturing. Post-annealing treatments increase crystallinity over that obtained at RT. This paper focuses on the maximum alternative-current magnetic susceptibility ( χ a c ) value of NiFe thin films with resonance frequency ( f res ) at low frequencies from 10 Hz to 25000 Hz. These results demonstrate that the χ a c of NiFe thin films increased with post-annealing treatment and increasing thickness. The NiFe (111) texture suggests that the relationship between magneto-crystalline anisotropy and the maximum χ a c value with optimal resonance frequency ( f res ) increased spin sensitivity at optimal f res . The results obtained under the three conditions revealed that the maximum χ a c value and optimal f res of a 1000 Å-thick NiFe thin film are 3.45 Hz and 500 Hz, respectively, following postannealing at T A = 250 ° C for 1 h. This suggests that a 1000 Å NiFe thin film post-annealed at T A = 250 ° C is suitable for gauge sensor and transformer applications at low frequencies.